FAKTOR-FAKTOR PENDORONG PENGUSAHA UMKM DALAM MENGAMBIL ATAU MENGGUNAKAN KREDIT USAHA RAKYAT (BRI) DI KABUPATEN SRAGEN - Liana Vivin Wihartanti (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The objective of this research is to know what is the most do minant factor that encourage UMKM enterpreneur stook the People’s Business Credit (KUR) at Bank BRI. The resultss howed that the most dominant factor that encouragethe UMKM entrepreneur stota keoruse the People’s Business Credit (KUR) in BRI loan interest rates lower by 37.31% followed by 29.85% recommended by a friend, easy administation of 17.91%, a longer repayment periodby 7.46% and good serviceat 7.46%. Keywords: Entrepreneur, People’s Business Credit (KUR), Micro, Small and Medium Enter prises (UMKM)